Circular patch antenna using metamaterial / Mohamad Zharif Mohamad Zani - Mohamad Zani, Mohamad Zharif (2009)
Recently the ancient Greek prefix, meta (means "beyond"), has been used to describe the composite materials with unique features[l]. Metamaterial is an arrangement of artificial structural elements designed to achieve advantageous and unusual properties[2]. Theoretically studies was done in 1967 by V.G. Veselago a physicist from Lebedjev Physical Institute in Moscow[2-7]. He examined the propagation of plane waves in a hypotical substance with simultaneous negative permittivity and permeability [7]. The researcher found that the pointing vector of the plane wave is anti parallel to the direction of the phase velocity, which is contrary to the conventional case of plane wave propagation in natural media[7]. The researcher also come out with the concept of left handed (LH) material and described their distinct properties, such as a reversed Doppler effect, a reversed Snell law and reversed Cerenkov radiation[5]. Although he suggested certain exotic solutions like gyrotropic plasmas, they still were not quite suitable due to many complications and no clear experimental evidence was obtain in this direction[2]. Furthermore it is likely that they are no way to obtain negative permeability at optical or higher frequency[2].